Dynamic mechanical behavior and energy dissipation characteristics of low-temperature saturated granite under cyclic impact loading - Huaqiao Xu; Chuanxin Rong; Bin Wang; Qinghe Zhang; Zhijun Shen; Yi Jin (Scientific Reports)
Abstract To investigate the dynamic mechanical behavior and energy dissipation characteristics of low-temperature rock samples under cyclic impact loading, a temperature-controlled impact system that combines Hopkins bars with a low-temperature compensation device was used. Five temperature gradients were confirmed via a trial impact test, and impact tests were conducted under two kinds of impact air pressures. The macroscopic damage characteristics of rock samples under cyclic impact at different temperatures, dynamic stress-strain curves, changes in peak stress and strain, energy dissipation, and cumulative damage at different temperatures, and the macroscopic and microscopic structural characteristics of low-temperature rock samples after cyclic impact were analyzed in combination with damage. The findings indicated that low-temperature saturated granite primarily experienced tensile damage under cyclic impact loading, with the required number of impacts increasing with decreasing temperature, and rock samples exhibited freeze-induced brittleness and significantly increased fragmentation. The dynamic stress-strain curve generally exhibited rebound characteristics in the post-peak stage. With an increasing number of cycles, an overall decrease in peak stress was observed, whereas the peak strain and cumulative specific dissipated energy exhibited opposite trends. This trend was more pronounced at lower temperatures, with a significant increase in peak strain and specific energy amplitude. In addition, the cumulative damage factor of the rock samples increased at lower temperatures, consistent with macroscopic damage characteristics, and exhibited a negative correlation with peak stress. The degree of crack extension in the macroscopic samples corresponded with the observed fracture changes. Microanalysis (SEM) indicated that decreasing temperature resulted in freeze brittleness of the fracture surfaces, characterized by reduced flatness and an expansion of brittle cracks across the damage surface. The slip separation phenomenon became increasingly pronounced, and these observations were positively correlated with the cumulative damage value.